2023
DOI: 10.1002/vms3.1270
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and public health relevance of enteric parasites in domestic dogs and cats in the region of Madrid (Spain) with an emphasis on Giardia duodenalis and Cryptosporidium sp.

Marta Mateo,
Ana Montoya,
Begoña Bailo
et al.

Abstract: BackgroundPet dogs and cats exert an unquestionable beneficial effect in the well‐being of their owners, but can also act as a source of zoonotic infections if improperly cared.ObjectivesWe investigated the occurrence, risk factors, genetic variability and zoonotic potential of intestinal parasites in dogs and cats attended in a clinical veterinary setting in Spain.MethodsCanine (n = 252) and feline (n = 35) faecal samples were collected during 2017–2019 and analysed by coproparasitological methods. A rapid la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…The zoonotic status of C. andersoni is uncertain ( Yang et al, 2021 ) and it has not been included in Table 2 , but there has been a single report of C. andersoni (0.1%; 1/676) in a shelter dog in the UK ( Rosanowski et al, 2018 ). Young age, presence of diarrhoea, and living in pet shops and shelters are risk factors associated with Cryptosporidium infection in cats and dogs ( Li et al, 2021a ; Mateo et al, 2023 ).…”
Section: Cryptosporidium In Cats and Dogsmentioning
confidence: 99%
See 4 more Smart Citations
“…The zoonotic status of C. andersoni is uncertain ( Yang et al, 2021 ) and it has not been included in Table 2 , but there has been a single report of C. andersoni (0.1%; 1/676) in a shelter dog in the UK ( Rosanowski et al, 2018 ). Young age, presence of diarrhoea, and living in pet shops and shelters are risk factors associated with Cryptosporidium infection in cats and dogs ( Li et al, 2021a ; Mateo et al, 2023 ).…”
Section: Cryptosporidium In Cats and Dogsmentioning
confidence: 99%
“…Assemblage A was the only assemblage identified in slum and stray dogs in Brazil ( Volotão et al, 2007 ; Fantinatti et al, 2018 ), domestic dogs in Jamaica ( Lee et al, 2017 ), and dogs in indigenous communities in Saskatchewan, Canada (32/32 typed isolates) ( Schurer et al, 2012 ). Subtyping of assemblage A in cats and dogs has identified mostly sub-assemblage AI, which is mainly confined to animal hosts ( Lalle et al, 2005b ; Souza et al, 2007 ; Volotão et al, 2007 ; Marangi et al, 2010 ; Zheng et al, 2015 ; Saleh et al, 2019 ; Mateo et al, 2023 ). However, some studies have identified sub-assemblage AII in cats and dogs (e.g.…”
Section: Giardia In Cats and Dogsmentioning
confidence: 99%
See 3 more Smart Citations